Simultaneous determination of chloroquine and colchicine co-nanoencapsulated by HPLC-DAD - Tamara Ramos Maciel, Camila de Oliveira Pacheco, Pietra Fonseca Ramos, Ana Claudia Funguetto Ribeiro, Renata Bem dos Santos, Sandra Elisa Haas (Journal of Applied Pharmaceutical Science, 2023)
Chloroquine (CQ) is an antimalarial drug that has several adverse effects and resistance. Colchicine (CC), demonstrates serious adverse effects, low oral bioavailability, and low therapeutic index. Co-encapsulation of CQ and CC in nanocapsules (NCs) could improve the physicochemical and pharmacokinetic characteristics and promote a synergistic effect of drugs for the treatment of malaria. The characterization of NCs, like the quantification of drugs, is an essential step. Therefore, the search for analytical methodologies is important. The objective was to develop and validate an analytical method to simultaneously quantify CQ and CC in an innovative NC formulation. NC formulations with co-encapsulated drugs were developed per nanoprecipitation. The method was developed through high-performance liquid chromatography using a reverse phase C18 column from Waters (4.6 × 300 mm × 5 μm). The mobile phase was acetonitrile, methanol, and 0.01% triethylamine (pH 3) (17:18:65); the detection wavelength was 350 nm. The response was linear from a range of 5–17.5 μg ml−1 for CQ and 1–12.5 μg ml−1 for CC. The drug content of CQ and CC was 100%, and the encapsulation rate was 99.47% ± 0.01% for CQ and 99.71% ± 0.03% for CC. The proposed method was selective, reproducible, linear, precise, accurate, robust, and applicable to simultaneously determine CQ and CC in polymeric NCs.
Keywords: Chloroquine, colchicine, nanocapsules, validation, LC method